LPS Induces Preeclampsia-Like Phenotype in Rats and HTR8/SVneo Cells Dysfunction Through TLR4/p38 MAPK Pathway - Fan, Minghua; Li, Xiaobing; Gao, Xiaolin; Dong, Lihua; Xin, Gang; Chen, Liqun; Qiu, Jianqing; Xu, Yongping (Frontiers in Physiology, 2019)
Accumulating evidence has shown that preeclampsia (PE) was associated with an aberrant maternal-fetal inflammatory response. In the present study, we first found that in human PE placentas levels of Toll-like receptor 4 (TLR4), phosphorylated p38 MAPK (p-p38) and inflammatory cytokines IL-6 and MCP-1 were significantly upregulated. Next, we demonstrated a notable increase in systolic blood pressure (SBP) and proteinuria in lipopolysaccharide (LPS)-treated pregnant rats; and concomitant high levels of TLR4 and p-p38 in these PE-like rat placentas, which led to aberrant overexpression of both IL-6 and MCP-1, as well as deficient trophoblast invasion and spiral artery (SA) remodeling; and these abnormalities were ameliorated by SB203580, a reported inhibitor of p38. In vitro we further confirmed that LPS triggered the activation of TLR4/p38 signaling pathway, which promoted trophoblast apoptosis and damaged trophoblastic invasion via downstream effectors IL-6 and MCP-1; these mutations were rectified by silencing this signaling pathway. These findings elaborated potential mechanisms that aberrant TLR4/p38 signaling might contribute to PE and LPS-induced PE-like symptom by damaging trophoblast invasion and SA remodeling via activating inflammatory cytokines including IL-6 and MCP-1.